2022
DOI: 10.3390/biomedicines10051083
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Different Tumor Biomarkers in Drug Resistance and Invasiveness in Primary and Metastatic Colorectal Cancer Cell Lines

Abstract: Protein expression profiles are directly related to the different properties of cells and are conditioned by the cellular niche. As an example, they are the cause of the characteristic cell plasticity, epithelium–mesenchymal transition (EMT), and drug resistance of cancer cells. This article characterizes ten biomarkers related to these features in three human colorectal cancer cell lines: SW-480, SW-620, and DLD-1, evaluated by flow cytometry; and in turn, resistance to oxaliplatin is studied through dose–res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…This data correlates with previous data from other research groups which connect chemoresistance, tumourigenicity potential, and slow-cycling in some tumour cells [44,46,54]. Several other markers (such as TROP2) could be involved in this chemorresistance process too, as has been recently identi ed by our group [55].…”
Section: Discussionsupporting
confidence: 92%
“…This data correlates with previous data from other research groups which connect chemoresistance, tumourigenicity potential, and slow-cycling in some tumour cells [44,46,54]. Several other markers (such as TROP2) could be involved in this chemorresistance process too, as has been recently identi ed by our group [55].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the relationship between TROP2 expression and resistance to oxaliplatin has been described in some CRC cells. It was suggested that the resistance was related to the TROP2-mediated enhancement of EpCAM-induced cell signaling [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many genes have been identified as potential inducers of epithelial-to-mesenchymal transition (EMT) in the progression of CC [ 29 , 30 ]. SSX2 expression was significantly higher in CC tissue samples with high disease grades than in NC tissue samples, suggesting that its expression is associated with cancer growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%